Brainstem serotonin amplifies nociceptive transmission in a mouse model of Parkinson’s disease - Zoé Grivet; Franck Aby; Aude Verboven; Rabia Bouali-Benazzouz; Benjamin Sueur; François Maingret; Frédéric Naudet; Thibault Dhellemmes; Philippe De Deurwaerdere; Abdelhamid Benazzouz; Pascal Fossat (npj Parkinson's Disease)
Abstract Parkinson’s disease arises from the degeneration of dopaminergic neurons in the substantia nigra pars compacta, leading to motor symptoms such as akinesia, rigidity, and tremor at rest. The non-motor component of Parkinson’s disease includes increased neuropathic pain, the prevalence of which is 4 to 5 times higher than the general rate. By studying a mouse model of Parkinson’s disease induced by 6-hydroxydopamine, we assessed the impact of dopamine depletion on pain modulation. Mice exhibited mechanical hypersensitivity associated with hyperexcitability of neurons in the dorsal horn of the spinal cord (DHSC). Serotonin (5-HT) levels increased in the spinal cord, correlating with reduced tyrosine hydroxylase (TH) immunoreactivity in the nucleus raphe magnus (NRM) and increased excitability of 5-HT neurons. Selective optogenetic inhibition of 5-HT neurons attenuated mechanical hypersensitivity and reduced DHSC hyperexcitability. In addition, the blockade of 5-HT2A and 5-HT3 receptors reduced mechanical hypersensitivity. These results reveal, for the first time, that PD-like dopamine depletion triggers spinal-mediated mechanical hypersensitivity, associated with serotonergic hyperactivity in the NRM, opening up new therapeutic avenues for Parkinson’s disease-associated pain targeting the serotonergic systems.